FREQUENCY AND ASSOCIATION OF COGNITIVE DYSFUNCTION IN SCHIZOPHRENIA: A CROSS-SECTIONAL STUDY FROM A TERTIARY CARE HOSPITAL IN PAKISTAN - Sher, Zainab; Suleman, Fawad; Iqbal, Samiya; Tahir, Amber; Rafi, Samia (Journal of Pakistan Psychiatric Society, 2025)
OBJECTIVE To assess the frequency of cognitive impairment and sociodemographic association among patients with schizophrenia presenting to a tertiary care hospital in Pakistan. STUDY DESIGN Descriptive cross-sectional study PLACE AND DURATION OF STUDY Outpatient Department of Psychiatry at Dr Ruth K.M. Pfau. Civil Hospital Karachi, Pakistan. The duration of the study was 6 months from February 6, 2020, to August 5, 2020. METHOD One hundred thirty patients with schizophrenia were assessed using the Urdu version of Montreal cognitive assessment questionnaire. RESULTS out of the 100 patients, 66 had significant cognitive impairment accounting for more than half of the study population at 50.8%. Age, duration of illness and gender showed significant association with cognitive dysfunction in these patients. CONCLUSION Cognitive dysfunction is a frequent finding in patients with schizophrenia. Future research is needed to investigate the factors increasing its risk. KEYWORDS Cognition; Memory; Outpatients; Pakistan; Schizophrenia; Tertiary Care Centres.